2016
DOI: 10.1002/stem.2388
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 Hexanucleotide Expansions Are Associated with Altered Endoplasmic Reticulum Calcium Homeostasis and Stress Granule Formation in Induced Pluripotent Stem Cell-Derived Neurons from Patients with Amyotrophic Lateral Sclerosis and Frontotemporal Dementia

Abstract: An expanded hexanucleotide repeat in a noncoding region of the C9orf72 gene is a major cause of amyotrophic lateral sclerosis (ALS), accounting for up to 40% of familial cases and 7% of sporadic ALS in European populations. We have generated induced pluripotent stem cells (iPSCs) from fibroblasts of patients carrying C9orf72 hexanucleotide expansions, differentiated these to functional motor and cortical neurons, and performed an extensive phenotypic characterization. In C9orf72 iPSC‐derived motor neurons, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
210
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(237 citation statements)
references
References 53 publications
12
210
2
Order By: Relevance
“…First, as opposed to findings in C9orf72 iPSC-derived neurons [1,13], we observed no increased levels of p62. However, p62 was upregulated by overexpression of Pur-alpha but not by the Pur-alpha deletion constructs lacking the G-rich or PUR2 domain.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…First, as opposed to findings in C9orf72 iPSC-derived neurons [1,13], we observed no increased levels of p62. However, p62 was upregulated by overexpression of Pur-alpha but not by the Pur-alpha deletion constructs lacking the G-rich or PUR2 domain.…”
Section: Discussioncontrasting
confidence: 99%
“…p62 is upregulated by Pur-alpha and prevents repeat RNA toxicity As p62 protein levels have previously been shown to be increased in C9orf72 iPSC-derived neurons [1,13], we investigated the possible involvement of p62 in our zebrafish model. Injection of sense repeat RNA did not modify the protein (Fig.…”
Section: The Protective Effect Of Pur-alpha Is Mediated By Its G-richmentioning
confidence: 99%
“…All other iPSC lines (Parkinson's disease and additional matched healthy control patients) were derived from skin biopsies or monocytes and reprogrammed in the same laboratory as described previously (33,35). iPSC lines were grown in mTeSR1 on Matrigel (Corning)-coated tissue culture dishes, passaged using 0.5 mM EDTA or using TrypLE, and plated with the Rho-kinase inhibitor Y-27632 (10 μmol/l).…”
Section: Methodsmentioning
confidence: 99%
“…Previously uncharacterized iPSC lines (JR036-2 and OX1-40) were characterized as described previously (35,40). Briefly, genome integrity was assessed by Illumina Human CytoSNP-12v2.1 beadchip array (∼300 000 markers) and analyzed using Karyostudio to generate karyograms and Genomestudio software (Illumina) to track samples to confirm parentage.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies reported that individual DPRs shared similar localization patterns but displayed different abundances: from highest to lowest are poly-GA, poly-GP, poly-GR, and poly-PA/poly-PR [89, 90]. Similar findings were also reported in C9 patient iPSCs derived neurons and C9 patient CSF (poly-GP was detected) [33, 49, 9194]. Fundamental questions regarding the role of these C9-DPRs remain: Is the presence of DPRs a mere pathological hallmark?…”
Section: Disease Mechanismsmentioning
confidence: 63%